Critical-feminist writing in the short stories Incompatibilidad and Equilibrio by Antonieta Rivas Mercado - Orellana Inostroza, Myriam Alejandra (Árboles y Rizomas, 2025)
This article engages in a critical-feminist reading of the short stories Incompatibilidad and Equilibrio by Antonieta Rivas Mercado, published in the context of the post-revolution in Mexico. Using the theoretical contributions of Latin American and European feminist literary criticism (Franco, 1986; Moi, 1989; Richard, 1993), I analyze gender issues based on the fictions of identity and the systems of power represented, thus identifying the strategies that break down the phalogocentric discourse. Specifically, I focus on the spatial imaginary and the study of voice (Medeiros, 2006). I argue that in both texts, the writer represents the subaltern condition of women (adult and young) and the effects of gender violence on their bodies, as a form of critical interpellation to the patriarchal and colonial Mexican culture. In this way, the symbolic transgressions that run through the stories generate a feminist twist by giving prominence to female voices that denounce both the violence and the power represented by the father-husband figure, evidencing the impossibility of women to comply with gender mandates. With this, Rivas Mercado opens a space of emancipatory imagination around women's bodies.
Keywords: Antonia Rivas Mercado; feminist writing; gender identity; subalternity; gender violence